2023
DOI: 10.1037/apl0001069
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on the crossover of workplace traumatic stress symptoms between partners.

Abstract: Workers who are exposed to severe situations such as death, harassment, and others’ suffering at work are vulnerable to symptoms of posttraumatic stress disorder (PTSD) and severe distress. This distress may extend to their intimate partners, despite their lack of firsthand experience with the traumatic stressors. Although theory and empirical research suggest that employees’ traumatic distress can transmit to their partners, the magnitude of these effects and when, how, and why intimate partners develop secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 111 publications
2
4
1
Order By: Relevance
“…This disconfirms the second hypothesis that relationship satisfaction reported by partners decreases as EMS workers’ PTSD symptom severity increases. This finding was inconsistent with prior literature (Regehr, 2005, Regehr et al, 2002; Sharp et al, 2022; Wang et al, 2022). Regarding social support, responses show that EMS workers’ PTSD symptomology does not impact the number of individuals within partners’ social support networks.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This disconfirms the second hypothesis that relationship satisfaction reported by partners decreases as EMS workers’ PTSD symptom severity increases. This finding was inconsistent with prior literature (Regehr, 2005, Regehr et al, 2002; Sharp et al, 2022; Wang et al, 2022). Regarding social support, responses show that EMS workers’ PTSD symptomology does not impact the number of individuals within partners’ social support networks.…”
Section: Discussioncontrasting
confidence: 99%
“…This confirms hypothesis 1, that as EMS workers report more severe PTSD symptoms, their partners also tend to report more severe PTSD symptoms. These findings are consistent with previous literature (Dirkzwager et al, 2005; Goff et al, 2006; Jordan et al, 1992; Wang et al, 2022). We also found that EMS workers’ PTSD severity most influenced partners’ intrusion and hyperarousal symptoms.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations